“It’s All About You Being Successful as a Student”: Mental Health and Wellness at a Post-Secondary Institution in Ontario: A Governmentality Analysis - Simar, Melinda (Université d'Ottawa / University of Ottawa, 2020)
A mental health crisis is happening on post-secondary campuses in Ontario today. Post-secondary institutions provide mental health services to students in an effort to respond to this crisis and manage students in distress. The management of students and the implementation of these mental health services is the main concern of this thesis, more specifically, the ways in which these services expose conscious and/or unconscious beliefs about student mental health. By extension, these beliefs constitute the ways in which we can think about, talk about, and know about patient safety. The object of study is the intersection of the neo-liberal university with the ‘good’ student and the resulting effects of this relationship on the development and implementation of mental health services. These intersections themselves create possibilities for acting on students in distress, but that also create unintended contradictions in the services themselves. An examination of this intersection can address a gap in the literature on post-secondary student mental health. The conceptual framework used in this study is primarily built from Michel Foucault’s concepts of subjectivity, and governmentality. The object of consideration is limited in this study to senior employees directly involved in student mental health at a university in Ontario. Documents are analysed to show how student mental health problems have been problematized nationally, provincially and locally and, thus, a behaviour to be regulated with governing practices. Data from interviews with senior University employees and observations of wellness events are analysed to examine the imbrication of advanced liberal rationalities and techniques in the implementation of mental health services on campus. The thesis argues that the development of these services is not an unproblematic process, whereby services and activities act simply as neutral tools to improve the mental health and well-being of students. Rather, these services aim to produce successful, enterprising students. Discourses of mental health and student success produce certain truths about practices and student subjectivities, obscuring and narrowing the definition of health and well-being and creating contradictions for students experiencing mental distress. In particular, this thesis shows how the University’s objectives for providing mental health services have implications for the development of mental health services and the governing of post-secondary in advanced liberal ways.
Keywords: Post-secondary students; Mental health; Governmentality; Discourse; Subjectivity; Neo-liberal university